Mental Health among Young Adults during the COVID-19 Pandemic: A Two-Wave Longitudinal Investigation. Issue 3 (3rd April 2023) - Măirean, Cornelia; Zancu, Simona Alexandra; Diaconu-Gherasim, Loredana R.; Brumariu, Laura E.
Abstract: This study aimed to assess changes in COVID-19 related factors (i.e. risk perception, knowledge about the virus, preventive behaviors and perceived efficacy) and mental health (i.e. psychological distress and positive mental health), in a sample of Romanian young adults attending college, assessed immediately after the national COVID-19 lockdown ended (Time 1) and six months after the end of the lockdown (Time 2). We also evaluated the longitudinal relations between COVID-19 related factors and mental health. The sample consisted of 289 undergraduate students (89.3% female, M age = 20.74, SD  = 1.06), who completed questionnaires assessing mental health and COVID-19-related factors via two online surveys, six months apart. The results showed that perceived efficacy and preventive behaviors, as well as positive mental health, but not psychological distress, decreased significantly over the six months period. Risk perception and perceived efficacy of preventive behaviors at Time 1 were positively related with the number of preventive behaviors measured six months later. Risk perception at Time 1 and fear of COVID-19 at Time 2 predicted the mental health indicators at Time 2. Public-health strategies should find the right balance in cultivating proper levels of risk perception that would be most beneficial for prevention of COVID-19 spread and mental health problems due to pandemic.